2023
DOI: 10.1097/pas.0000000000002097
|View full text |Cite
|
Sign up to set email alerts
|

PEComa of the Adrenal Gland

Craig B. Wakefield,
Peter M. Sadow,
Jason L. Hornick
et al.

Abstract: PEComas are a family of mesenchymal neoplasms composed of histologically distinctive perivascular epithelioid cells which demonstrate myomelanocytic differentiation. PEComas of the adrenal gland are very rare and can represent a considerable diagnostic challenge given their morphologic overlap with more common adrenal cortical neoplasms. We present the clinicopathologic features of 7 primary adrenal PEComas. The cohort comprised 5 male and 2 female patients with a median age of 63 years (range: 31 to 71 y). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Perivascular epithelioid cell tumors (PEComas) are a family of mesenchymal neoplasms, originating from the perivascular epithelioid cell line (PEC), and usually exhibiting distinctive histological, immunological, and genetic characteristics of melanocytic and smooth muscle markers. 1,2 Recent studies showed positive 18 F-FDG uptake in malignant PEComas and their metastatic foci and negative uptake in benign PEComas. [3][4][5][6][7] In the present case, only the primary lesion of this PEComa with diffuse metastases did exhibit elevated glucose consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perivascular epithelioid cell tumors (PEComas) are a family of mesenchymal neoplasms, originating from the perivascular epithelioid cell line (PEC), and usually exhibiting distinctive histological, immunological, and genetic characteristics of melanocytic and smooth muscle markers. 1,2 Recent studies showed positive 18 F-FDG uptake in malignant PEComas and their metastatic foci and negative uptake in benign PEComas. [3][4][5][6][7] In the present case, only the primary lesion of this PEComa with diffuse metastases did exhibit elevated glucose consumption.…”
mentioning
confidence: 99%
“…Other than showed intense uptake in the aforementioned FDG-avid lesions (SUV max of 19.1, see arrow in B), axial fused PET/CT images of 18 F-FAPI PET/CT revealed diffuse nodular hypermetabolic foci in the right submandibular gland (SUV max of 18.4, see arrow in C), bilateral thyroid gland (SUV max of 15.1, see arrow in D), anterosuperior mediastinum (SUV max of 25.2, see arrow in E), and multiple muscle tissue and/or subcutaneous fats (SUV max of 8.3, see arrow in F and G). Subsequently, the patient underwent CT-guided biopsy of the left abdominal wall lesion; immunohistochemical examination showed positive staining for HMB45, MelanA, SMA, and Ki-67 (<3%), which confirmed the diagnosis of perivascular epithelioid cell neoplasm.Perivascular epithelioid cell tumors (PEComas) are a family of mesenchymal neoplasms, originating from the perivascular epithelioid cell line (PEC), and usually exhibiting distinctive histological, immunological, and genetic characteristics of melanocytic and smooth muscle markers 1,2. Recent studies showed positive 18 F-FDG uptake in malignant PEComas and their metastatic foci and negative uptake in benign PEComas [3][4][5][6][7].…”
mentioning
confidence: 99%